Types of waste identification in Perintis Lake as an ecotourism conservation efforts Bone Bolango District, Gorontalo Province - Mohamad, Danial; Lanti, Syahrul (Genbinesia Journal of Biology, 2024)
Perintis Lake is a lake area with potential for ecotourism. However, as activities progress, some areas have become littered with garbage. Therefore, the purpose of this study focuses on identifying the types of waste and determining the most common types of waste in the Perintis Lake area. This study uses a quantitative descriptive research method by identifying the types of waste scattered in the lake area using a sampling method categorized based on the size characteristics of mega-debris (>1 m), macro-debris (2.5 cm–1 m), meso-debris (5 mm–2.5 cm), and micro-debris (0.33 mm–5 mm). Based on the research activities, the sample collections locations are in two different transect areas, namely the Perintis Lake tourist area and the lake area directly facing residential areas. The total identification results obtained from both transects consist of 266 types of waste in five different categories: plastic waste, rubber, metal, glass, wood, and derivatives. Among the findings, plastic waste is the most dominant type of waste in the lake area, totalling 218 types. Furthermore, in terms of waste characterization based on size, macro-debris is the most abundant category in the lake area, particularly plastic waste, with a total of 168. The abundance of plastic waste in the research location is influenced by indiscriminate disposal by visitors to the environment and also by household activities directly facing the Perintis Lake area, resulting in an increasing spread of waste distribution over time.